VD_FINDINFO Jug / 2013 / 79 vom 12. Dezember 2012 - VD Tribunal cantonal (2012)
FARDEAU DE LA PREUVE, ASSURANCE-INCENDIE PUBLIQUE, ASSURÉ, CHOSE MOBILIÈRE, DOMMAGE, PERTEARGENT | 27 LAIEN, 35 LAIEN, 38 LAIEN, 50 LAIEN, 6 LAIEN, 69 LAIEN